Study of The Economic Consequences of SCR Hypocrisy Behavior - Shi, Yanlong; Li, Jiang Li (International Journal of Management and Education in Human Development, 2022)
The company assumes that social responsibility is the highest embodiment of the value of the company, and when the company assumes the responsibility of the enterprise. Because of some subjective and objective factors, the company will lead to deviating from the original good behavior, showing a situation of different words and deeds, that is, to obtain the value increase brought by the social responsibility, and without bearing any form of expenses. So this paper is divided into three parts. First of all, the background of SCR's hypocrisy behavior is introduced, and then we further define the hypocrisy behavior of enterprises and the motivation and harm of hypocrisy behavior. Finally, through the two perspectives of the government and society, the corresponding supervision and management measures are put forward. It provides a theoretical basis for society and the masses to discover the hypocritical behavior of enterprises in time.